Emigracyjne eseje (?) Jerzego Pietrkiewicza - Olejniczak, Józef (Archiwum Emigracji, 2020)
THE EMIGRÉ ESSAYS OF JERZY PIETRKIEWICZ The article offers an analysis of Jerzy Pietrkiewicz’s comments on Polish literature, in particular his remarks on the nature of the relation between poetry and European identity, religion and technological development. Moreover, it demonstrates that some of Pietrkiewicz’s insights preceded the well-known statements made later by literary theorists and writers themselves.